Integrating Authentic Assessment into Learning Evaluation to Strengthen School Quality Assurance: A Library Research - Indah, Ariski Nuril; Julaiha, Siti (Journal of Educational Management Research, 2025)
This study aims to analyse the integration of authentic assessment into learning evaluation as a strategic effort to strengthen school quality assurance. This research employed a library research design by systematically reviewing relevant books, nationally accredited journals, reputable international journals, and educational policy documents. Data were analysed using content analysis techniques to identify conceptual patterns related to authentic assessment, learning evaluation, and school quality assurance systems. The findings indicate that authentic assessment plays a significant role in providing comprehensive, valid, and meaningful data on students’ cognitive, affective, and psychomotor competencies. Its integration into learning evaluation supports both internal and external quality assurance systems by enhancing accountability, transparency, and continuous improvement in schools. Furthermore, authentic assessment encourages reflective teaching practices, strengthens evidence-based decision-making, and aligns learning outcomes with real-world competencies. The implications of this study suggest that schools need to systematically institutionalize authentic assessment within their evaluation policies as part of a sustainable quality assurance culture. This study contributes theoretically to the development of educational quality assurance models and practically to improving evaluation practices in schools.